IMPLEMENTASI SHALAT MENURUT SAYYID ABDULLAH DALAM KITAB SAFINATUS SHALAH PADA JAMAAH MAJELIS MIFTAHUL KHOIR - Munzi, Ahmad; Muiz, Abdul (Institut PTIQ Jakarta, 2024)
This study examines the implementation of prayer according to Sayyid Abdullah in the Book of Safinatus Sholah in the congregation of Majlis Miftahul Khoir. Using a qualitative descriptive research method, this study aims to evaluate the understanding and implementation of congregational prayer based on the guidance of the book. The results of the study indicate that the congregation's understanding of prayer material including the requirements of prayer, the pillars of prayer, and matters that invalidate prayer is quite good. However, in its implementation, it was found that the congregation had not been able to fully implement it perfectly, especially in terms of the requirements of prayer, the pillars of prayer and matters that invalidate prayer. Supporting factors for religious study activities include support from the village government, elders, and all elements of society, while inhibiting factors include weather conditions and the age factor of the congregation, the majority of whom are elderly. There is a difference in the level of understanding and implementation between congregations who regularly attend religious studies and those who rarely attend. The study concludes that overall, the congregation has an awareness of the importance of understanding prayer and can implement it quite well in everyday life according to the guidance of the Book of Safinatus Shalah.